Intention to use green products among consumers - Mohammad Hasbullah, Shaik Ismail (2014)
The study of consumer behavior towards green products has become a very important research nowadays. Every human being requires a good quality of environment and good health status in order to guarantee a useful life for self and family. The needs for green products in the daily lives of individuals are necessary today. So, a deeper study of the intention to use green products may be a reference to consumers and organizations. This study aimed to investigate the relationship between attitudes, subjective norms, and perceived control behavior with the intention to use. The researcher has distributed a 120 set of questionnaires. Only one set of survey questions unsuccessful return. All 119 of the returned questionnaires could be used for analysis of the study. Among the methods used in this research are independent sample t-test, one- way ANOVA, Pearson correlation and multiple regressions. The results showed that all independent variables are significant and seen have influenced intention to use green products among consumers. Among the three independent variables, the attitude is most influenced intention to use green products because it has the highest regression. This means, the higher the positive attitude of consumers towards green products, the higher their intention to use the product. As a result, retailers and marketers should increase consumers‟ desire to use green products by creating an effective marketing strategy. In addition, other parties such as government and non-governmental organizations should also strive to increase positive attitudes of consumers towards green products. The discussion of the implications and suggestions for future research are also described at the end of the study.